Macrophages and the Viral Dissemination Super Highway - Klepper, Arielle (EC Microbiol, 2015)
Monocytes and macrophages are key components of the innate immune system yet they are often the victims of attack by infectious agents. This review examines the significance of viral infection of macrophages. The central hypothesis is that macrophage tropism enhances viral dissemination and persistence, but these changes may come at the cost of reduced replication in cells other than macrophages.